526 The development and evaluation of an Australian child pedestrian safety campaign. (1st September 2016) - Murray, Clare; Lewis, Ioni; Lennon, Alexia; Vuong, Kim; Haworth, Narelle
Abstract : Background: Road crossing is a complex activity and children's risk of pedestrian crashes is greater due to their underdeveloped perceptual and cognitive skills. This project involved the design and evaluation of a child pedestrian safety campaign, guided by an Extended Theory of Planned Behaviour. The evaluated component consisted of a short (30 sec) video that sought to raise parental road safety awareness and deliver the safety message that parents should hold children's hands in carparks and while crossing the road. Methods: 400 parents of children 3–9 years responded to an on-line survey. Parents were randomly assigned to either Intervention (n = 200) or Control (n = 200) groups. Both groups received the same attitudinal and demographic questions. Intervention parents also viewed a 30 sec safety message video and received questions about message interpretation, acceptance, and intentions to perform the suggested behaviour (holding hands). Results: Following one-off exposure to the video, though not statistically significant, the Intervention group reported stronger intentions to hold their child's hand when crossing a road (M = 4.78, SD = 0.55), or in a carpark (M = 4.73, SD = 0.63) in the coming month, than parents in the Control group (M 4.71, SD = 0.62 and M = 4.72, SD = 0.54 respectively). Also, the Intervention group reported higher levels of Perceived Behavioural Control (roads, M = 4.63, SD = 0.55; carparks, M = 4.65, SD = 0.57) than parents in the Control group (roads, M = 4.51, SD = 0.61; carparks, M = 4.54, SD = 0.60). Intervention group parents reported the video was appropriate in content (M = 4.39, SD = 0.74) and tone (M = 4.19, SD = 0.80), and that they were likely to adopt the strategy presented (M = 4.20, SD = 0.96), which they reported as effective (M = 4.04, SD = 0.92). Conclusions: Although parental intentions were high in both groups, these findings provide some support for the persuasiveness of the campaign video. Intervention group parents reported consistently higher intentions to hold their children's hands, and believed that this strategy was something that they could enact easily. The implications of these findings on future research and practice for child pedestrian safety are discussed.